Artistic Strategies in the Face of the Questioning of Hegemonic Masculinity in Western Society: From the crisis at the end of 20th Century to its Resurgence Today - Alfonso Del Río Almagro; Mariano Manuel Pastrana de la Flor (Masculinities and Social Change, 2018)
This article sets out a study about the capacity of the artistic discourse to question the representation of concepts that support traditional hegemonic masculinity in occidental society and its mechanisms of reproduction, from the crisis of the masculinities of the 90s to the present, with the appearance of new emerging hegemonic masculinities. If at the end of the 20th century we witnessed cultural transformations that transgressed the normative ideal of Occidental masculinity, making possible the proliferation of new Masculinities, the sociocultural changes that occurred in the first decades of the 21stcentury have ended up impacting on the values underlying the dominant masculinity, provoking a new resurgence and strengthening of conservative masculinities models. For this purpose, based on the contributions of those of the Studies of Masculinity, we developed a critical analysis of the contemporary artistic strategies that, both at the end of the XX century and at present, have intervened in the construction processes of normative masculinity, altering their representation codes, visibilizing proposals of new peripheral masculinities and favouring alternative models against not hegemonic masculinities and more plural, inclusive and egalitarian.